Case report: 18F-FDG PET/CT in pulmonary enteric adenocarcinoma - Luo, Zhe-Huang; Luo, Xiao-Yan; Luo, Xiu-Qin; Jin, Ai-Fang; Zeng, Qing-Yun (Frontiers in Oncology, 2024)
Pulmonary enteric adenocarcinoma (PEAC), an uncommon variant of lung cancer, presents significant diagnostic challenges due to its overlapping characteristics with colorectal adenocarcinomas. We present a case of a 55-year-old non-smoking female patient diagnosed with PEAC. The patient’s initial symptoms included fever, cough, and sputum production, with air space consolidation on CT, leading to an initial diagnosis of pneumonia. Sputum culture after admission showed no growth of bacteria and fungi. Anti-inflammatory therapy was not ideal. Subsequent bronchoscopy with endobronchial ultrasound and biopsy confirmed the diagnosis of PEAC. Gastroscopy and colonoscopy yielded negative results, and a PET/CT scan revealed an FDG-avid lesion in the right middle lobe, with no other significant hypermetabolic gastrointestinal lesions, thereby excluding an extrapulmonary primary gastrointestinal malignancy. The patient was ultimately staged as PEAC (T4N1M0, stage IIIb). She declined anti-tumor therapy and experienced clinical deterioration during follow-up. This case report expands the radiological spectrum of PEAC, adds to the limited literature, and emphasizes the role of 18F-FDG PET/CT in diagnosing such diseases. It also underscores the importance of a multidisciplinary approach in the management of PEAC.